Unlocking the power of public awareness: paving the way for sustainable wetland management in Anzali, Iran - Allahyari, Mohammad Sadegh; Marzban, Soroush; Gonzalez-Ollauri, Alejandro; Nazari, Elham; Ben Hassen, Tarek; Surujlal, Jhalukpreya (Frontiers in Environmental Science, 2024)
The Anzali Wetland, located in the Guilan Province of Iran, is a vital ecosystem with significant ecological value. However, it faces numerous environmental challenges due to pollution, habitat degradation, and unsustainable resource use. This paper aims to assess the awareness and perceptions of local communities regarding the Anzali Wetland, Iran, and its management and how these factors might influence the implementation of the CEPA program. A quantitative survey based on a structured questionnaire was designed and administered to local communities within the wetland’s watershed. The data were analyzed using descriptive statistics. The results indicate that local communities have limited knowledge about the wetland, often associating it solely with Anzali Lagoon. Despite this lack of awareness, most participants recognize the wetland’s importance in conserving wildlife. Further, participants identified domestic and industrial wastewater pollution as the most significant threat to the wetland. Additionally, education at the school level, the Internet, and virtual networks were perceived as effective means of raising awareness among the local population. The study highlights the importance of increasing public participation and interaction among different social groups to enhance awareness of the wetland’s value and environmental issues. It also emphasizes the need for coordinated efforts among stakeholders in wetland management and policy-making, including government agencies and civil organizations. By examining the significance of public awareness in the Iranian context, the study provides unique insights into wetland conservation efforts in a specific geographical and ecological setting. Furthermore, by considering the perceptions and opinions of these stakeholders, the study offers a holistic understanding of the diverse perspectives and interests related to wetland conservation, which adds depth and richness to the analysis.